Diagnosis of Acute Rubella infection during early Pregnancy in Iraq - Abdullah, Basima A.; Mohammed, Hulia K.; Salman, Hayfaa D. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: To study prevalence and method of diagnosis of acute rubella Infection during early pregnancy in Iraq. Patients and Methods: Clinical signs and symptoms of acute rubella infection were looked for in (170) pregnant women looked before (12) weeks of gestation .Serial rubella specific IgG and IgM serological testing was done in these (170) women before (12) weeks of pregnancy, after (3) weeks, and again at (18-20) weeks of gestation. Results: Three woman had clinical signs and symptoms of rubella infection from (26) woman were IgM positive at (9) weeks of pregnancy; (94) were IgG +ve but IgM –ve initially and also on repeat sampling after (3) weeks; while (50) women were nonimmune (IgG and IgM negative) in the first trimester, after (3) weeks and again at (18-20) weeks. Conclusion(S): Acute rubella infection was diagnosed by serial serologic screening in (26) women in early pregnancy.